Nesnovna kulturna dediščina in muzeji - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2020)
The article talks about the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage from 2003 and its influence on the activities of museums. A number of museum practices relating to intangible heritage are presented, which had been present before, but the Convention placed an even greater emphasis on them. The way intangible heritage is included in museum activities is illustrated with the example of the Slovene Ethnographic Museum as a national museum and as the national Coordinator for the Safeguarding of the Intangible Cultural Heritage.
Keywords: muzeji; nesnovna kulturna dediščina; Slovenski etnografski muzej; Unesco